Miller Fisher syndrome and COVID-19: is there a link?. Issue 8 (11th August 2020) - Ray, Amanda
Abstract : Beyond the typical respiratory symptoms and fever associated with severe acute respiratory syndrome, we may still have much to learn about other manifestations of the novel SARS-CoV-2 infection. A patient presented with Guillain-Barré syndrome in China with a concurrent SARS-CoV-2 infection. The following case report looks at a patient presenting with the rare Miller Fisher syndrome, a variant of Guillain-Barré while also testing positive for COVID-19.